Model Pembelajaran Snowball Throwing Di Sekolah Dasar - Hery Setiyawan (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is apreliminary research that contains efforts to implement the snowball throwing learning model at the elementary level, especially in grade 4. This study also aims to determine student responses to the application of the snowball throwing learning model at the elementary school level. This study used a research design with the